Stuck how to WIN in business by understanding LOSS - Grady, Victoria; McCreesh, Patrick (Productivity Press, 2022)
Stuck: How to WIN in Business By Understating LOSS addresses a critical concept that closes a gap in popular business publications. Many books tell leaders and managers the process of how to change their organizations. However, many of these books lack a key mechanism for understanding human interactions. The mechanism is a biological function developed through evolution called attachment - the human need to connect to different tangible and intangible objects for support. Attachment is the reason that people connect with leaders and corporate culture, but also what creates a deep sense of loss during even the smallest changes. Stuck offers a complete understanding of attachment and how it impacts individuals, relationships, and organizations. It is based in over 20 years of research and practical experience; data from nearly than 20,000 respondents globally; and findings from two previous books (The Pivot Point and Workplace Attachment) and over 60 articles and presentations. But Stuck is not an academic study. It is a practical guide for leading the brain through change. For the first time, the authors tell stories that demonstrate the research and offering a prescriptive roadmap for how to leverage attachment research to drive business success. Work is changing. Every day new companies, technologies, and ideas emerge that impact how, where, and most importantly, why we work. Despite this exciting evolution, people remain the heart of change. People are tricky. People don't seem to evolve as fast as our global environment. We get stuck. Leaders, managers, and teammates struggle with the resistance and get frustrated. Frustrated people impact the performance of every organization. The authors set out to answer a seemingly simple question - How does understanding loss help us achieve business wins? They believe that the answer is a deeply human problem. In fact, it is a deeply biological problem. It is rooted in our brain and the way our brain interacts everything in the world, even work. It is how our brain controls our interactions with technology, our connection with peers, our perception of leaders, the way we view our organization, and even our connection to the community where we live. All of these factors impact how we perform as individuals at work and ultimately how organizations perform in the global marketplace. The root of the challenge is the human need to connect to different tangible and intangible objects for support. The basis of the need for support is grounded in our need for attachment. Attachment behavior is an instinctual response born out of our earliest days of life and impacts how we connect and interact with the world around us. Those who learn to understand loss through attachment behavior and the attachments of others will succeed. The book is based on over 20 years of research into attachment in the workplace. Stuck is a set of fascinating literature that is brought forward through highlighting the stories (ironically) we have grown accustomed to "leaning on" for answers. Additionally, this book will provide original data-based evidence from assessments conducted with nearly 20,000 respondents and original stories from the application of attachment concepts in more than 150 organizations across all sectors around the globe. It will shine a light on attachment and use it as a lens to better understand our workplace. Stuck provides not only the deep lessons from the authors' research, but also prescriptive steps for readers to use the lessons of attachment in their own work. In this way, the book will serve as a guide to those leaders, managers, and employees who are feeling stuck and don't know how to get loose
Title details screen
Keywords: Psychology, Industrial; Attachment behavior; Organizational change; Object Attachment; Organizational Innovation; Psychologie du travail; Attachement; Changement organisationnel; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Behavior; BUSINESS & ECONOMICS; Workplace Culture